Approximation by composition of Szász-Mirakyan and Durrmeyer-Chlodowsky operators - Izgi, Aydin (Eurasian Mathematical Journal, 2012)
We establish some approximation properties in weighted spaces and we give a Voronovskaya type asymptotic formula for the composition of the Szász-Mirakyan and Durrmeyer-Chlodowsky operators.